Vpliv standardov MOD na slovenski sistem socialne varnosti - Strban, Grega (Delavci in delodajalci, 2019)
The ILO minimum standards of social security might not be of the newest date, but they are not to be disregarded. Analysed are the standards binding for Slovenia. The characteristics of the right to social security are emphasised, which is based on solidarity, the connective tissue of every successful society. It is established that the minimum standards importantly shape definitions of social risks, rights and duties stemming from the social security system and procedures for their enforcement. They could play a vital role when delineating between public and private responsibility in cases of sickness or old-age.
Keywords: brezposelnost; delovno pravo; health insurance; ILO; ILO standards; Mednarodna organizacija dela; mednarodne konvencije; pension insurance; pokojninsko zavarovanje; social security; socialna varnost; unemployment insurance; zdravstveno zavarovanje